2014
DOI: 10.1536/ihj.13-367
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Chronic Kidney Disease and Anemia at Admission on In-Hospital Outcomes After Primary Percutaneous Coronary Intervention for Acute Myocardial Infarction

Abstract: SummaryCardiorenal anemia syndrome has recently been receiving greater attention; however, data regarding the relationship between chronic kidney disease (CKD)/anemia on presentation and in-hospital outcome in patients with acute myocardial infarction (AMI) undergoing primary percutaneous coronary intervention (PCI) are still limited in Japan.A total of 1,447 primary PCI-treated AMI patients were classified into 4 groups according to the presence of CKD and/or anemia on hospital admission (with CKD/with anemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
4
25
0
1
Order By: Relevance
“…4) In this study, erythrocyte creatine was measured with other hemolytic markers in patients with aortic stenosis and it was found that lactate dehydrogenase and erythrocyte creatine were significantly higher and haptoglobin was lower in patients with aortic stenosis as compared with the controls. Since patients with renal failure and recent bleeding were not included in this study, 25,26) these data indicate that high-velocity jets ejected through the narrow orifice caused intravascular hemolysis in patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…4) In this study, erythrocyte creatine was measured with other hemolytic markers in patients with aortic stenosis and it was found that lactate dehydrogenase and erythrocyte creatine were significantly higher and haptoglobin was lower in patients with aortic stenosis as compared with the controls. Since patients with renal failure and recent bleeding were not included in this study, 25,26) these data indicate that high-velocity jets ejected through the narrow orifice caused intravascular hemolysis in patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…5) Dyslipidemia was defined as a total cholesterol level ≥ 220 mg/dL or low-density lipoprotein cholesterol level ≥ 140 mg/dL or medical treatment for dyslipidemia or a history of dyslipidemia. 5,6) Diabetes mellitus was defined as a hemoglobin A1c level ≥ 6.5% (as NGSP value) or medical treatment for diabetes mellitus or a history of diabetes mellitus. 5) We also calculated the estimated glomerular filtration rate (eGFR) from the serum creatinine level, age, weight, and gender using the following formula; eGFR = 194 × Cr -1.094 × age -0.287 (male), eGFR = 194 × Cr -1.094 × age -0.287 × 0.739 (female).…”
Section: Methodsmentioning
confidence: 99%
“…7) Additionally, anemia per se was associated with higher in-hospital mortality and poor long-term outcome in patients presenting with STEMI undergoing primary PCI. 35,36) Because of the high prevalence of these predictors in our study the mortality rate in our study was high (15.7%). This is higher than in the national cardiovascular collaboration network or the French registry which reported a short-term mortality of 3.8% and 3.4%, respectively.…”
Section: )mentioning
confidence: 55%